A Project feasibility study on NutriCubes - Coeli, Clare T.; Legasto, Pamela Kathleen P.; Soto, Patty Claire M.; Yu, Gemma L. (College of Engineering, 1998)
The Food Nutrition Research Institute (FNRI) of the Department of Science and Technology (DOST) has developed a food supplement that is rich in Vitamin A and fortified with thiamin and riboflavin. Taking the form of a bouillon cube, this supplement may be used as a nutrient and flavor enhancer. It was renamed by the proponents as NutriCubes. The market competitor analysis, which included examinations of industry, competitor, demand, and supply data, yielded the following market share and sales plan of NutriCubes. Furthermore, the Market Study identified the consumer group Mothers as the target market for the NutriCube and the National Capital region (NCR) as its target market area. A comprehensive marketing strategy worth Php 2,246,258.00 for the first year was arranged. In the Technical study, the group was able to gather much needed information regarding the processes, operations and projected costs of all relevant technical inputs needed to produce NutriCubes. Decisions were made in choosing the alternatives wherein the bases included cost, quality and capacity. Process alternatives were evaluated for the manufacture of NutriCubes. Based on costs of materials, machines, labor and utilities, it was determined that the company should produce squash flour and purchase all other raw materials. An optimal production plan was devised based on the cost of machines versus that of labor. Production will be six (6) days a week for the projected time period. For the squash flour production, the entire process will require 15 hours with workers reporting to work at various hours of the day. This holds for each five (5) years except for the second where production will be for 17 hours. Bouillon production on the other hand takes eight (8) hours a day for each of the five (5) years except the second where one hour of overtime will be required. Additional workers and machines will be used from the third to the fifth year to enable the company meet demand. A plant site was chosen based on given criteria, which include location of suppliers, location of customers, road networks, utilities, size of land, and land rate. The NutriCube factory will be a 1,200-square meter land at 124 Quirino Highway, Novaliches, Quezon City. Purchasing the plant site will cost the company Php 11,400,000.00, the amount of which is payable in five years or less. The total start-up cost is pegged at Php 75,815,191.24 for the company's first year of operation. Organization and Management study indicated that the corporation-type is the best form of ownership for the company. Relevant features of this type of ownership include entity, life, liability, pooling of capital, pooling of management talents and business contacts, attraction of loan financing, and business growth. In addition, 15 various managerial and staff positions were assigned based on minimum company needs. Salaries were determined based on industry standards with the succeeding monthly salaries: President, Php 25,000; 3 Managers, Php 20,000 each; HRD personnel, Php 17,000; 2 Supervisors, Php 15,000 each; Treasurer, Accountant, and 2 Salespersons Php 12,000 apiece; Secretary, Php 7,000; Janitor, Php 4,500; 2 Security guards, Php 5,200 each and the 30 production workers receiving the minimum wage equal to Php 5,148 per month. Salaries increase by 10% annually. For the Financial Study, the company has identified an initial total project cost amounting to Php 49,010,914.36, which is based on the half0year start-up cost of the project. The figure was rounded to Php 50,000,000.00 and was used as the project's needed investment capital. The company will be loaning 45% of its capita, or Php 22,500,000.00 from Metrobank. This loaning agent was chosen for its low interest rate and its more suitable collateral requirements. The company will be offering capital stock worth 55% of its initial capital requirements, or Php 27,500,000.00. There would be 1,100,000 shares of capital stock worth Php 25.00 each. Using sensitivity analysis and financial ratios, the project was assessed, and it was concluded that it is financially feasible. Its payback period is 3.03 years, its IRR is 56%, and its net present value is calculated at Php 4,611,290.51. In inclusion, the Social Profitability Study yielded several benefits that the company would effect. Benefits to the community would include health awareness and improved health among NutriCube users, and the possibility of lowering prices of products in the same line. Employment of 44 employees will also be generated for the first year. For the local industry, the purchase of raw materials worth of Php 40,547,962.25 and office and plant supplies worth Php 101,251.35 will be earned for the first year. Lastly, the government will gain additional revenue through corporate income tax totaling Php 13,919,213.29 and municipal taxes worth Php 665,262.50. Collection of withholding tax equals to Php 518,555. These values are for the first year alone and are increasing for the projected life of the company.